Spectral Observations of Optical Emissions Associated With Terrestrial Gamma‐Ray Flashes. Issue 4 (20th February 2021) - Heumesser, Matthias; Chanrion, Olivier; Neubert, Torsten; Christian, Hugh J.; Dimitriadou, Krystallia; Gordillo‐Vazquez, Francisco J.; Luque, Alejandro; Pérez‐Invernón, Francisco Javier; Blakeslee, Richard J.; Østgaard, Nikolai; Reglero, Victor; Köhn, Christoph
Abstract: The Atmosphere‐Space Interactions Monitor measures Terrestrial Gamma‐Ray Flashes (TGFs) simultaneously with optical emissions from associated lightning activity. We analyzed optical measurements at 180–230, 337, and 777.4 nm related to 69 TGFs observed between June 2018 and October 2019. All TGFs are associated with optical emissions and 90% of them are at the onset of a large optical pulse, suggesting that they are connected with the initiation of current surges. A model of photon delay induced by cloud scattering suggests that the sources of the optical pulses are from 0.7 ms before to 4.4 ms after the TGFs, with a median of −10 ± 80 µs, and 1–5 km below the cloud top. The pulses have rise times comparable to lightning but longer durations. Pulse amplitudes at 337 nm are ∼3 times larger than at 777.4 nm. The results support the leader‐streamer mechanism for TGF generation. Plain Language Summary: Terrestrial Gamma‐Ray Flashes (TGFs) are short bursts of high‐energy radiation produced in thunderstorms, first observed from astrophysical spacecraft during the 1990s. This study characterizes optical emissions from lightning associated with these flashes in multiple wavelengths to help finding their production mechanism. The data are collected by space based instruments aboard the International Space Station as it passes over the major thunderstorm regions of the Earth. We find that TGFs are associated with propagation of intracloud lightning in the upper cloud levels. With the help of a model of light propagation through a cloud, we estimate the source of the respective optical emissions to be 1–5 km below the cloud tops. By investigating TGFs and their connection to lightning, we can understand the energy and timescales of lightning better, eventually leading to a better understanding of cloud physics and thunderstorms in general. Key Points: We present the first statistical analysis of emissions at 180–230, 337, and 777 nm coincident with TGFs as measured by a single platform 90% of TGFs occur at the onset of large‐amplitude optical pulses supporting the streamer‐leader mechanism for TGF generation The sources of the emissions are estimated to be 1–5 km below the cloud tops